Diffuse midline glioma metastasis to the peritoneal cavity via ventriculo-peritoneal shunt: Case report and review of literature. (September 2019) - Stephens, Sean; Tollesson, Gert; Robertson, Thomas; Campbell, Robert
Highlights: Extraneural glioma metastasis via ventriculoperitoneal shunts is extremely rare. First case of diffuse midline glioma H3 K27M-mutant metastatic to peritoneum reported. Glioma peritoneal metastasis are typically seen in children with high-grade lesions. Poor prognosis typically seen amid peritoneal metastasis of gliomas. Abstract: Extraneural dissemination of primary intracranial tumours to the peritoneal cavity via ventriculoperitoneal shunts is rare, with medulloblastoma and germ-cell tumours most common and gliomas seldom implicated. This report is the first described case of a diffuse midline glioma H3 K27M-mutant disseminating to the peritoneal cavity via a shunt. A four-year-old female presented with a large solid-cystic lesion centred on the suprasellar cistern, histologically revealed to be diffuse midline glioma H3 K27M-mutant. The patient received multiple courses of radiotherapy to the primary lesion and metachronous spinal metastases, and underwent bilateral ventriculoperitoneal shunts. She presented fourteen months following diagnosis with acute hydrocephalus and massive ascites revealed to be due to histologically confirmed intra-abdominal glioma metastasis secondary to shunting. Bilateral ventriculoatrial shunts along with targeted abdominal radiotherapy and repeated ascitic drainage were performed. The patient died one month later. A literature review demonstrated that intra-abdominal glioma metastasis is an extremely rare complication of cerebrospinal fluid diversion predominantly affecting paediatric patients with high-grade lesions within the first year after diagnosis and portends poor prognosis. Predisposition to metastasis is likely associated with tumour proximity to cerebrospinal fluid spaces and tumour biology. Contraindicating shunting in the presence of an intracranial tumour cannot be endorsed but rather shunt-related metastasis should be an acknowledged risk, and not-to-be-forgotten presentation.